2019
DOI: 10.3389/fendo.2019.00533
|View full text |Cite
|
Sign up to set email alerts
|

A1C Underperforms as a Diagnostic Test in Africans Even in the Absence of Nutritional Deficiencies, Anemia and Hemoglobinopathies: Insight From the Africans in America Study

Abstract: Introduction: To improve detection of undiagnosed diabetes in Africa, there is movement to replace the OGTT with A1C. The performance of A1C in the absence of hemoglobin-related micronutrient deficiencies, anemia and heterozygous hemoglobinopathies is unknown. Therefore, we determined in 441 African-born blacks living in America [male: 65% (281/441), age: 38 ± 10 y (mean ± SD), BMI: 27.5 ± 4.4 kg/m 2 ] (1) nutritional and hematologic profiles and (2) glucose tolerance categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…of access to care [1]. However, failure of fasting plasma glucose (FPG) and HbA 1c , to detect early T2D in Africans must be considered [3,4]. As early T2D in Africans often occurs with only a 2 h glucose (2 h-PG) 11.1 mmol/L, performance of an OGTT is pivotal [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…of access to care [1]. However, failure of fasting plasma glucose (FPG) and HbA 1c , to detect early T2D in Africans must be considered [3,4]. As early T2D in Africans often occurs with only a 2 h glucose (2 h-PG) 11.1 mmol/L, performance of an OGTT is pivotal [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Briker et al also found similar disparities in the African population [12]. Using HbA1c as the sole diagnostic tool in nutritionally replete Africans without anemia or heterozygous hemoglobinopathy would underdiagnose 60% of diabetics and 40% of prediabetics.…”
Section: Genetics and Hba1c: The Implications In Sct Patientsmentioning
confidence: 84%
“…However, 11 studies showed that using an NGSP-certified machine without HbS interference gave conflicting results, as seen in Table 3. One study stated that HbA1c was higher [4], three stated the same [3,12,16], five stated lower [5,6,11,14,17], one stated higher to lower [13], and one stated the same to lower [15], when compared to a hematologically normal patient.…”
Section: Comparison Of Studies Using An Ngsp-certified Methods With Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The Africans in America cohort was established to assess risk for diabetes and heart disease in African-born blacks living in the USA 20 21. Recruitment was by newspaper advertisements (45%), participant referrals (30%), presentations at community events, flyers and electronic outreach.…”
Section: Methodsmentioning
confidence: 99%